An Enriched Perspective towards Corrective Feedback - Vindas Carmona, Jaz (Universidad de Costa Rica, Sede de Occidente, 2022)
Three aspects that teachers should consider when planning and providing corrective feedback (CF) in English as a Second Language teaching are analyzed in this essay: the extent to which the instructional context and focus influence teachers’ decision about the timing and type of corrective feedback, how the analysis of one’s error sources can contribute to the provision of CF, and in what way teachers can balance their preferences and those of their students towards CF techniques. The link between error correction and the instructional context in which the CF techniques used on teachers when they were learners and students’ expectations, background, and current abilities is uncovered in this essay. Furthermore, this essay examines the importance of analyzing one’s error sources in oral and written productions in order to promote autonomous students while strengthening their abilities through relevant material as their mistakes were anticipated. Finally, the significance of promoting a safe environment in which learners may interact with their teacher and providing scaffolded assistance through different explicit and implicit CF strategies are revealed to highlight the significance of integrating students’ and teachers’ preferences for specific types of CF and timing.